Navigating the digital frontier during the COVID‐19 pandemic and EVALI epidemic: The impact of social media on public health - Chimwemwe Ngoma; Apatsa Matatiyo; Gabriel Ilerioluwa Oke; Yusuff Adebayo Adebisi; Deborah Oluwaseun Shomuyiwa (Wiley, 2024)
Abstract This commentary explores how social media influenced public health narratives and responses during two recent health crises, the COVID‐19 global pandemic and the e‐cigarette or vaping product use-associated lung injury (EVALI) epidemic. In the context of COVID‐19 pandemic, social media played a dual role, acting as both a catalyst for information dissemination and a breeding ground for misinformation. This situation highlighted the challenges public health institutions face in navigating online narratives and maintaining public trust during crises. Conversely, the EVALI epidemic shed light on how social media narratives can impact public perception and policy decisions. Initially, attributed to nicotine vaping, subsequent investigations revealed that contaminated cannabis oils containing vitamin E acetate were the actual cause, leading to shifts in public discourse and regulatory considerations. This case underscores the importance of accurate information dissemination to prevent misinterpretations that could negatively impact public health interventions. The commentary also highlights the evolving nature of online narratives and the need for public health agencies to adapt their strategies continually. Fact‐checking programs, public health campaigns, and collaborations with technology companies emerged as critical strategies to combat misinformation and promote evidence‐based practices. However, addressing the root causes of misinformation, such as addressing distrust in institutions, remains an ongoing challenge requiring multifaceted approaches. Looking ahead, controlling online narratives during health crises will continue to present challenges as social media platforms evolve and new challenges emerge. Finding a balance between information sharing and privacy protection while fostering digital literacy skills among the public will be paramount. Collaborative efforts among public health agencies, technology companies, and communities will be essential in navigating and managing online narratives effectively. This commentary underscores the interplay between social media and public health, highlighting the need for strategic interventions, accurate information dissemination, and ongoing adaptation to address emerging challenges in the digital age.